2011
DOI: 10.1007/s10900-011-9428-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Cigarette Smoking Among Immigrant Children and Girls in Hong Kong: An Emerging Public Health Issue

Abstract: Despite global progress in tobacco control, data are needed for subgroups with increased risk of tobacco use for more effective smoking prevention. Survey data from a random sample of 6,486 youth in grades 7, 8 and 9 were derived from the project Chinese Student Health Survey. Prevalence and hazards of smoking onset were compared by gender and immigrant status. Mediation analysis was used to assess factors that may mediate the impact of immigrant status on smoking. Immigrant students had a much higher risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Findings of this study clearly demonstrate the need for specific tobacco control measures in China, particularly behavioral intervention to reduce adolescents' receptivity and anti-tobacco social marketing to counter-attack tobacco advertising. The high levels of media receptivity reported in our study also support the conclusion by others that the legal measures of banning tobacco advertisement in China are ineffective (Li et al, 2009;Yang et al, 2010;Lau, Chen, & Ren, 2012;Yang et al, 2012). In this case, an alternative approach for the Chinese Ministry of Health to control tobacco would be to strengthen anti-tobacco social marketing, an evidence-based and cost-effective strategy for tobacco control demonstrated in the West (Sutfin, Szykman, & Moore, 2008;Scheier & Grenard, 2010;Buller et al, 2011).…”
Section: Media Receptivity and Cigarette Smokingsupporting
confidence: 88%
See 2 more Smart Citations
“…Findings of this study clearly demonstrate the need for specific tobacco control measures in China, particularly behavioral intervention to reduce adolescents' receptivity and anti-tobacco social marketing to counter-attack tobacco advertising. The high levels of media receptivity reported in our study also support the conclusion by others that the legal measures of banning tobacco advertisement in China are ineffective (Li et al, 2009;Yang et al, 2010;Lau, Chen, & Ren, 2012;Yang et al, 2012). In this case, an alternative approach for the Chinese Ministry of Health to control tobacco would be to strengthen anti-tobacco social marketing, an evidence-based and cost-effective strategy for tobacco control demonstrated in the West (Sutfin, Szykman, & Moore, 2008;Scheier & Grenard, 2010;Buller et al, 2011).…”
Section: Media Receptivity and Cigarette Smokingsupporting
confidence: 88%
“…Data were collected using the Chinese Student Health Behavior Questionnaire (CSHBQ), a paper-and-pencil survey we previously used in China (Zheng, Sussman, Chen, Wang, Xia et al, 2004;Lau, Chen, & Ren., 2012). The participants filled out the questionnaire in their classrooms.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the traditional Chinese culture discourages girls to smoke, relative to mainland China, the low gender ratio or more girls smoking in Hong Kong, Macau and Taiwan may be a reflection that more girls in these cities consider them equal to boys with regard to smoking. Previous research also showed increased smoking among girls in Hong Kong [40].…”
Section: Differences In the Prevalence Of Health Behavior Measuresmentioning
confidence: 80%
“…Perceived parental monitoring was assessed using a 3-item instrument with 5-point Likert scale (alpha = 0.67) [36,40]. Scale scores were derived by summing up individual items such that higher scores indicating closer parental monitoring as perceived by youth.…”
Section: Variables At the Student Levelmentioning
confidence: 99%